BACK-END SYSTEM DESIGN BASED ON REST API - Hendrik Fery Herdiyatmoko (Politeknik Bisnis Indonesia, 2022)
Back-End is a logical space with the functionality and operation of a software application or information system. Currently, SMA Xaverius 1 Palembang does not yet have a rest server-based application whose background can be accessed by a multi-platform rest client. Therefore, an application based on the RESTful rest api based back-end was built. This RESTful application or REST Server provides data to be accessed by the REST Client using data exchange in JSON format using the HTTP protocol built using the Laravel Framework. The Laravel framework provides a mechanism for building REST Servers via the Rest Server library that supports a full RESTful server implementation. The results of this research have been successful. A Laravel 7-based REST Server application has been built which provides endpoints in the form of json and status codes which can later be accessed by multi-platform rest clients. Through the application based on the back-end rest api, the results from the endpoint get a response from the server in the form of json that supports interoperability.